The prospect of using ozone-safe refrigerants with low global warming potential in scroll compressors. Part 1 - V. A. Pronin; A. V. Kovanov; E. A. Kalashnikova; V. A. Tsvetkov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2021)
The Montreal Protocol and the Kigali Amendment have determined the need and deadlines of the replacement of hydro fluorinated refrigerants. Substances of natural origin with a low global warming potential are becoming an alternative to hydrofluorocarbons that are being withdrawn from circulation. Such an alternative corrects the vector of development of refrigeration equipment and entails the need to adapt or create new models of equipment taking into account the excellent properties of new refrigerants. However, the consumer’s choice is still based on the efficiency, cost and reliability of the equipment. Having studied the possibility of using new refrigerants, in the fields of using a scroll compressor, from the point of view of the operational properties of substances, we also noted some aspects of the influence of their thermodynamic and thermophysical properties on the working processes and design of compressor elements. Thus, we present a comparative analysis of the practical application and further prospects for the using of refrigerants in a scroll compressor, highlighting the current directions of studying this issue.